Effect of operational parameters on solid state fermentation of cassava peel to an enriched animal feed - Jamal, Parveen; Tijani, Ruqayyah I. D.; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed (Asian Network for Scientific Information, 2012)
Response surface methodology based on the Face-Centered Central Composite Design (FCCCD) was employed to determine the effects of process conditions on the production of an enriched animal feed from cassava peel by a locally isolated white rot fungus Panus tigrinus (M609RQY). Seventeen experimental runs based on three parameters (pH, inoculum size and moisture content) as designated by FCCD were carried out under solid state fermentation. The effect of these parameters on lignin degradation in cassava peel was evaluated. Statistical analysis of the results showed that, only moisture content exerted a highly significant effect (p<0.01) on lignin degradation. The optimum parameter combination was found at 70% v/w of moisture content, 6% v/w inoculum size and pH of 5.30. Under this optimum, 50.62% lignin loss was obtained. This study presents a viable option to the management of cassava peel for production of value-added-product animal feed